Early Repolarization Pattern and Idiopatic Sustained Monomorphic Ventricular Tachycardia: an Infrequent Combination - Pinos Vásquez, Javier; Leiria, Tiago Luiz Luz; Kruse, Marcelo Lapa; de Lima , Gustavo Glotz (JOURNAL OF CARDIAC ARRHYTHMIAS, 2021)
Malignant early repolarization as cause of sudden death has taken on great importance in recent years. It has been described as an entity capable of producing ventricular arrhythmic events, causing from episodes of syncope to sudden cardiac death. Ventricular fibrillation is the typical arrhythmia in these patients, with no clear relationship to date with idiopathic monomorphic ventricular tachycardia. Electrocardiographic markers related to the development of arrhythmic events in early repolarization syndrome have been described. They seem not only related to the development of ventricular fibrillation, but also to sustained monomorphic ventricular tachycardia, as is the case described in the article.